Type and evolution stage of Hungarian oil shale kerogens - Hetényi Magdolna; Pápay László (University of Szeged, Department of Mineralogy, Geochemistry and Petrology Szeged, 1986)
The insoluble organic matter of some Hungarian oil shales (Upper Pannonian, maar type: Pula, Gérce, Várkesző, and Miocene, jlagoon-type: Mecsek, Várpalota, Mátraszele) were investigated. In spite of the same age and similar formation processes the maar-type oil-shale kerogens are different: the Pula kerogen proved to be an algal-derived organic matter of type I, of high conversion and H/C ratio, and good petroleum potential. On the contrary, the organic matter of Várkesző oil shale corresponds to type n and can be interpreted by presence of terrestrial plant remnants in the precursor material. The considerable difference between the Pula and Várkesző oil shales during the thermal decomposition in the evolution paths, apparent activation energy (Pula: 146 kJmol- 1 and Várkesző 75 kJmol- 1 ) and in the ratio of the gas and oil phases formed can be interpreted by the presence of terrestrial plant remnants in the precursor material of the Várkesző oil shale. The kerogen of Gérce oil shale can be considered as a transition between type I and II. The lagoon-type oil chales contain kerogen of type II. The Corgcontent and petroleum potential, as well as the H/C atomic ratio and the HC-yield of the Várpalota oil shale is fairly high. During the pyrolysis it generates considerable amount of oil. The petroleum potential of oil shales from Mecsek and Mátraszele corresponds rather to a source rock of good quality.
Keywords: Természettudományok; Föld- és kapcsolódó környezettudományok